2013
DOI: 10.1002/aenm.201300937
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐Grained and Nanostructured AgPbmSbTem+2 Alloys with High Thermoelectric Figure of Merit at Medium Temperature

Abstract: . IntroductionThermoelectric (TE) materials have drawn increasing attention because of their potential applications in energy harvesting and electronic cooling devices. [ 1,2 ] The performance of a thermoelectric material is defi ned by its dimensionless fi gure of merit ZT = α 2 ( ρ κ ) −1 T , where α is the Seebeck coeffi cient (also called as thermopower), T is the absolute temperature, ρ is the electrical resistivity, and κ is the thermal conductivity. [ 3 ] Extensive research has been carried out attempti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 42 publications
2
26
0
Order By: Relevance
“…This value has achieved over 20% improvement when compared with reported bulk Cu 2 Se [13]. In fact, this value is comparable to those highest thermoelectric materials reported so far [2,4,29,30]. To fundamentally understand our observed exceptional thermoelectric performance, detailed structural characterizations were performed on the sintered pellets.…”
Section: Resultssupporting
confidence: 82%
“…This value has achieved over 20% improvement when compared with reported bulk Cu 2 Se [13]. In fact, this value is comparable to those highest thermoelectric materials reported so far [2,4,29,30]. To fundamentally understand our observed exceptional thermoelectric performance, detailed structural characterizations were performed on the sintered pellets.…”
Section: Resultssupporting
confidence: 82%
“…9,26,27 Second, the incorporation of SiC nanoparticles refined the grains, leading to enhanced grain boundary scattering effect to reduce the lattice thermal conductivity in this polycrystalline LAST alloy. Such an effect was also realized in our previous work, 18 in which the microstructure was refined in a different way. Third, but importantly, the SiC nanodispersion effect of reducing lattice thermal conductivity of the present nanocomposites should be enhanced at the interfaces between the nanodispersions and the matrix by the existence of mismatched layer or spacing, as shown below.…”
supporting
confidence: 71%
“…16 Especially, in PbTe-based AgPb m SbTe mþ2 (LAST, lead-antimony-silver-tellurium) compounds, a high ZT value up to 1.7 at 700 K was achieved by Hsu et al in 2004. 17 Previous studies 9,17,18 indicated that the endotaxial nanostructure is very effective in enhancing ZT value of LAST alloys, such as the phase-segregation with the presence of embedded nanodots (appear to be rich in Ag and Sb) in the PbTe matrix, which are believed to play an important role in scattering phonons without influencing electron transport meanwhile. However, one may worry about the stability of such a nanostructure when used for a long time at high temperatures.…”
mentioning
confidence: 99%
“…However, the ZT value of n -type TE oxides (e.g., SrTiO 3 11, ZnO12, CaMnO 3 13) is still lower in terms of assembling a practical oxide-based TE device due to its mediocre electrical conductivity σ (~100–200 S.cm −1 ) and/or high thermal conductivity κ = ( κ l + κ e ) (~2–10 W.m −1 .K −1 ). In this regard, two main strategies have recently been applied to improve the ZT : One is to enhance the power factor ( S 2 σ ) by tuning the carrier concentration14, or band engineering151617 and the other is to reduce κ L by enhancing phonon scattering through solid solutions and nanostructuring2318. In fact, our previous work reveals that thermal conductivity can be reduced from 3 W m −1 K −1 (micron sample) to 2.2 W m −1 K −1 (nanostructured sample) in In 2 O 3 -based ceramics19.…”
mentioning
confidence: 99%